Outage probability based power allocation and relay selection algorithm in cooperative communication - Li-yue SUN; Xiao-hui ZHAO; Ming GUO (Tongxin xuebao)
The relay selection and power optimization of multi-relay cooperative communication network under a joint sum power constraint was considered.A low complexity lay selection and power allocation algorithm was also pro-posed in amplify-and-forward cooperative network aiming at minimizing the probability of system outage.In this scheme,optimal power allocation among source and relay nodes was conducted.According to the SNR,an optimal relay node set was selected and a power allocation factor leading to lower system outage probability was obtained by steepest descent method.This algorithm did not need large quantity of l statistical information and equal power condition.It can obtain the best set of relay nodes under optimal power allocation only by solving the arranged matrix on the basis of Sig-nal to Noise Ratio.Simulation results show that the proposed relay select and power allocation algorithm,under the same conditions,compared in the outage probability in erent relay node set among several algorithms,achieves better performance in outage probability and power efficiency.